IMPLIKASI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 77/PUU-IX/2011 DALAM PELAKSANAAN PENYELESAIAN PIUTANG PADA BANK BADAN USAHA MILIK NEGARA (Suatu Penelitian di Kantor Pelayanan Kekayaan Negara dan Lelang Banda Aceh) - Riyanieta Setiya Putri, Iman Jauhari, Sri Walny Rahayu. (Jurnal Ilmu Hukum, 2016)
Abstract : Banking activities in Indonesia in terms of ownership consists of three (3) bodies, namely Bank Company Limited which is a State Owned Enterprise (SOE), Non-SOE Banks or private banks, and as belong to the cooperative. Handling of receivables SOE before the Constitutional Court decision number 77/PUU-IX/2011 , submitted to PUPN accordance with Regulation Number 33 in 2006 on Procedures for the Elimination of Receivables Country/Region. After the Court's decision, the state bank cannot perform the elimination of receivables completely because there are still multiple interpretations of the definition of state receivables under Law Number 1 of 2004 on State Treasury. The purpose of study is to determine the mechanism of settlement of accounts in state banks before and after the birth of a Constitutional Court decision Number 77/PUU-IX/2011, barriers and settlement mechanism. The method used for the study is normative. Before the birth of the Decision of the Constitutional Court, the settlement of the state receivables submitted to PUPN and regulated in Government Regulation Number 33 of 2006, PMK Number 87/PMK.07/2006 and the Minister of Finance Letter Number S-324/MK.01/2006. After the verdict, all the process is handed over to state-owned banks. Barriers faced are covering from internal and external. The obstacles are overcame with training and knowledge sharing to the aperture KPKNL professionally in order to accomplish its task.Keywords : Settlement Accounts Receivable, Bank Owned Enterprises. Abstrak : Kegiatan perbankan di Indonesia dari segi kepemilikan terdiri dari 3 (tiga) bagian, yaitu Bank PT Persero yang merupakan Badan Usaha Milik Negara (BUMN), bank swasta, dan milik koperasi. Pengurusan piutang bank BUMN sebelum putusan Mahkamah Konstitusi nomor 77/PUU-IX/2011, diserahkan kepada Panitia Urusan Piutang Negara sesuai Peraturan Pemerintah Nomor 33 Tahun 2006 tentang Tata Cara Penghapusan Piutang Negara/Daerah. Setelah putusan tersebut, bank BUMN tidak dapat melakukan penghapusan piutang secara tuntas karena masih ada multi tafsir terhadap definisi piutang Negara berdasarkan Undang-Undang Nomor 1 Tahun 2004 tentang Perbendaharaan Negara. Tujuan penelitian yaitu untuk mengetahui mekanisme penyelesaian piutang pada bank BUMN sebelum dan sesudah lahirnya putusan Mahkamah Konstitusi Nomor 77/PUU-IX/2011, hambatan dan mekanisme penyelesaiannya. Metode penelitian yang digunakan yaitu metode yuridis normatif. Sebelum Putusan Mahkamah Konstitusi tersebut, penyelesaian piutang negara diserahkan pada PUPN dan diatur dalam PP Nomor 33 Tahun 2006, PMK No. 87/PMK.07/2006 dan Surat Menteri Keuangan RI Nomor S-324/MK.01/2006. Setelah putusan, semua prosesnya diserahkan kepada bank BUMN. Hambatan yang dihadapi mencakup internal dan eksternal. Penyelesaian hambatan dilakukan dengan pelatihan dan sharing knowledge kepada aparatur KPKNL agar menyelesaikan tugasnya secara profesional.Kata kunci : Penyelesaian Piutang, Bank BUMN.